De novo transcriptome assembly and identification of the gene conferring a "pandan-like" aroma in coconut (Cocos nucifera L.). (November 2016) - Saensuk, Chatree; Wanchana, Samart; Choowongkomon, Kiattawee; Wongpornchai, Sugunya; Kraithong, Tippaya; Imsabai, Wachiraya; Chaichoompu, Ekawat; Ruanjaichon, Vinitchan; Toojinda, Theerayut; Vanavichit, Apichart; Arikit, Siwaret
Highlights: A de novo assembly of transriptome from coconut endosperm was performed. The gene associated with a "pandan-like" aroma (2AP) in coconut was identified. A SNP found in the CDS of the gene (CnAMADH2) caused an amino acid change (P442A). The amino acid change might result in an unstabilized dimer conformation of AMADH. A functional marker for detecting the aroma trait in coconut was developed. Abstract: Thailand's aromatic coconut ( Cocos nucifera L.) is a special type of green dwarf coconut, the liquid endosperm of which is characterized by a pleasant "pandan-like" aroma due to the presence of 2-acetyl-1-pyrroline (2AP). The aim of this study was to perform a de novo assembly of transriptome from C. nucifera endosperm and to identify the gene responsible for 2AP biosynthesis. CnAMADH2 was identified as an ortholog of the rice aromatic gene and a G-to-C substitution found in exon 14 was associated with 2AP content in the aromatic green dwarf coconut accessions. The base substitution caused an amino-acid change, alanine-to-proline, at position 442 (P442A). The presence of P at this position might alter the steric conformation at the loop region and subsequently result in an unstabilized dimer conformation that could lower AMADH enzyme activity. Among AMADH/BADH protein sequences in different plant species, the P442A mutation was found exclusively in aromatic coconut. The PCR marker developed based on this sequence variation can perfectly detect the aromatic and non-aromatic alleles of the gene. This study confirms the hypothesis that plants may share a mechanism of 2AP biosynthesis. This is the first identification of the gene associated with 2AP biosynthesis in a tree plant.